Dillenia suffruticosa extract inhibits proliferation of human breast cancer cell lines (MCF-7 and MDA-MB-231) via induction of G2/M arrest and apoptosis - Armania, Nurdin; Saiful Yazan, Latifah; Ismail, Intan Safinar; Foo, Jhi Biau; Tor, Yim Sim; Ishak, Nurshafini; Ismail, Norsharina; Ismail, Maznah (MDPI, 2013)
The present research was designed to evaluate the anticancer properties of Dillenia suffruticosa extract. Our focus was on the mode of cell death and cell cycle arrest induced in breast cancer cells by the active fractions (designated as D/F4, D/F5 and EA/P2) derived from chromatographic fractionation of D. suffruticosa extracts. The results showed that the active fractions are more cytotoxic towards MCF-7 (estrogen positive breast cancer cells) and MDA-MB-231 (estrogen negative breast cancer cells) as compared to other selected cancer cell lines that included HeLa, A459 and CaOV3. The induction of cell death through apoptosis by the active fractions on the breast cancer cells was confirmed by Annexin V-FITC and PI staining. Cell cycle analysis revealed that D/F4 and EA/P2 induced G2/M phase cell cycle arrest in MCF-7 cells. On the other hand, MDA-MB-231 cells treated with D/F4 and D/F5 accumulated in the sub-G1 phase without cell cycle arrest, suggesting the induction of cell death through apoptosis. The data suggest that the active fractions of D. suffruticosa extract eliminated breast cancer cells through induction of apoptosis and cell cycle arrest. The reason why MCF-7 was more sensitive towards the treatment than MDA-MB-231 remains unclear. This warrants further work, especially on the role of hormones in response towards cytotoxic agents. In addition, more studies on the mechanisms underlying the induction of apoptosis and cell cycle arrest by the plant extract also need to be carried out.